LOCAL CULTURE AND STUDENT LEARNING PATTERNS IN LEARNING HISTORY: BUDAYA LOKAL DAN POLA BELAJAR SISWA DALAM PEMBELAJARAN SEJARAH - Muhammad Rafi Rabbani; Ninit Setyanti Latif; Leli Yulifar (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the forms of local culture within the school environment, students’ learning patterns in history learning, and the role of local culture in shaping students’ learning patterns at SMA Islam Cipasung. The study employed a qualitative approach with an educational ethnography design. Data were collected through participant observation, in-depth interviews, and document analysis. Data analysis was conducted through the stages of domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The findings reveal that the local culture at SMA Islam Cipasung is formed through a combination of Sundanese cultural values and pesantren traditions that emphasize religiosity, respect for teachers, mutual cooperation, and communal learning habits. Local culture plays a role in shaping students’ learning patterns through three main mechanisms: as a cognitive schema, a motivational regulator, and an interactional protocol. The integration of local culture into history learning enhances student engagement, strengthens historical understanding, and makes learning more contextual and meaningful. However, the study also found challenges in the form of dense school and pesantren activities that affect students’ physical condition and learning concentration. This study confirms that local culture is an essential component in history learning and should be integrated responsively into teachers’ pedagogical practices